Medical ethics assessment scale for sports: A new tool - AGOPYAN, ANİ (North-West University, Potchefstroom, 2020)
The purpose of this study was to develop the Medical Ethics Assessment Scale for Sports (MEASS) and to asses the vison of amateur level competitor athletes, using this scale, about level of compliance with professional ethical principles of their health professionals and the sports medicine organisations with which they come in contact. The study was conducted on 400 participants (nfemale =145; nmale =255) aged 16-35 from different sports. MEASS was constructed with 13 items and three factors: ‘Not harming the patient’s body’, ‘Informing the patient’, and ‘Maintaining patient’s privacy and right to choose care’. The validity value was found to be 0.795. The exploratory factor analysis showed all three factors had eigenvalues greater than 1.0 (55.7% variance). Cronbach‘s Alpha reliability (α) correlation coefficient was 0.725. These results showed that the scale is suitable for factor analysis and reliable. The MEASS can be used as a new measurement tool to evaluate the ethics of health professionals and organisations. The results also demonstrated that athletes feel well-informed and unharmed by their physicians, but would prefer more control over their care choices and how their personal information is used. © 2020, North-West University, Potchefstroom. All rights reserved.
Keywords: Ethics; Health; Medical ethics; Medicine; Sports